Function and Psychotherapy of Chronic Suicidality in Borderline Personality Disorder: Using the Reinforcement Model of Suicidality - Hennings, Johannes M. (Frontiers in Psychiatry, 2020)
Although great advancements in evidence-based therapies, chronic suicidal patients with Borderline Personality Disorder (BPD) still challenge our mental health system. While BPD patients continue suffering from distress and aversive emotions, therapists and relatives feel often stunned and helpless when confronted with suicidality resulting in interruption of therapies, repeated presentations to emergency rooms and referrals to hospitals. Reviewing the current knowledge of the functions and background of non-suicidal self-injury, we learned that reinforcement mechanisms play an important role to understand why individuals act in deliberate self-mutilation. While individual motives for non-suicidal self-injury and suicidal behavior including suicidal ideations can differ, the principle mechanisms appear to be transferrable. Elucidating the individual motives and function of suicidal behavior is an important therapeutic step, giving us access to very central maladaptive schemes and false believes that we need to address in order to reduce chronic suicidality in BPD patients. This Perspective aims to give a better idea of what is behind and what are the differences between non-suicidal self-injury, suicidal ideations and suicide attempts. It further integrates recent developments of behavioral science in a reinforcement model of suicidality that can provide therapists a practical armamentarium in their work with chronic suicidal clients.